Innovative work behaviour: a bibliometric analysis and future research directions / Khalijah Mohd Nor … [et al.] - Mohd Nor, Khalijah; Wan Hashim, Wan Nor Syazana; Jislan, Fatanah; Ahmad, Nurbarirah; Abdul Rahim, Ramita (2023)
The main driver of organization development and competitive advantage is innovation. The increases in change in a variety of business sectors throughout the world, demanding that businesses and institutions come up with innovative solutions to problems in order to perform well. In this paper, a bibliometric analysis is conducted to determine the evolution of publications on innovative work behaviour. Our sample is composed of all the documents from the SCOPUS database for the period 2000–2023. As a result of the findings, the research on innovative work behaviour has grown exponentially in Pakistan, China, and Malaysia. The analysis also reveals the most cited authors and papers, including the most frequent subject area in this research, highlighting that current trend studied are in the area of business and management and social sciences. Potential research directions are also provided by suggesting specific research themes and conceptual approaches. This analysis has direct implications for academics in positioning their future research in innovative work behaviour as it is very necessary among employees to face the dynamic business environment. Employee creativity serves as a source of original ideas that the team or the entire business may use, and it is crucial to the survival and sustainability of the organization.